Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.2116/analsci.14.831
|View full text |Cite
|
Sign up to set email alerts
|

Atomization Mechanisms of Gold from Thermally Decomposed and Crudely Roughened Pyrolytically Coated Graphite Furnaces Using Electrothermal Atomization

Abstract: Studies of atomization mechanism of gold and silver in electrothermal atomization seek a better understanding of the atomic vapor formation process and the type of interactions taking place between the analyte and the surface of the atomizer. This type of information can lead to logical approaches for improvement of the technique or the method of analysis. Arthur and Cho 1 reported the adsorption and desorption kinetics of gold on a single graphite crystal where adsorbed atoms (adatoms) can move on the single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…4B). The similar phenomenon is observed also for Au (see, e.g., [38]). At the same time, for Cu (Fig.…”
Section: The Order Of Release Of Free Atomsupporting
confidence: 81%
“…4B). The similar phenomenon is observed also for Au (see, e.g., [38]). At the same time, for Cu (Fig.…”
Section: The Order Of Release Of Free Atomsupporting
confidence: 81%
“…When gold atoms are releasd from microdroplets, a mass dependency of E a was reported, 2,4 while no dependency was observed for gold desorption from monolayers on the graphite surface. 3 The independence of E a from the injected mass of gold (Table 4) is supported by the desorption of gold from monolayers.…”
Section: Resultsmentioning
confidence: 85%
“…Although the E a did not reach a constant value for gold deposited on a thermally decomposed, pyrolytically coated graphite (PG) surface, the E a reached a constant value for gold deposited on a crudely roughened PG surface, corresponding to adatoms of gold at active sites. 3 At this time a lowertemperature shift of the atomic absorption signal of gold was observed.…”
mentioning
confidence: 88%
“…Gaseous dissociation of SeO 2 (where analyte loss may occur) is followed by the first-order desorption of Se from carbon. Imai et al (91) used Raman spectrometry to study the effects of multiple firings and physical roughening on the inner wall of a Massmann-type furnace and investigated the atomization of Au. This was of interest, since previous studies on the atomization of Au have indicated desorption from microdroplets or from adatoms, depending on analytical conditions and, particularly, on the number of active sites on the graphite surface.…”
Section: Atomization Mechanismsmentioning
confidence: 99%